An Introduction to Unexpected Grief for Pre‐Licensure Nursing Students: A Simulation and Interprofessional Expert Panel Regarding Fetal Demise. Issue 6 (November 2015) - Knight, Candace C.; Dailey, Kelly D.; Currie, Erin R.
Abstract : N/A: To provide pre‐licensure nursing students with a safe, clinically appropriate learning experience in unexpected grief in the obstetric setting, a simulation scenario involving intrauterine fetal demise was implemented. Narrative feedback from students following the simulation indicated that the death of a fetus and the grief of the family were upsetting. For this reason, an interdisciplinary panel to provide pastoral care and grief support was invited to take part in debriefing during subsequent simulations. Evaluations of subsequent simulations were positive.